ANALISIS KEBUTUHAN PENGEMBANGAN VIDEO PEMBELAJARAN MATA KULIAH PROGRAM LINIER - Wulandari, Nourma Pramestie; Salsabila, Nilza Humaira; Kurniati, Nani (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2021)
Linear Programming is a course under the scope of algebra that must be mastered by mathematics education students. The low ability to solve linear programming problems can affect student performance when they become a teacher. This study aims to analyze the need for developing learning videos in Linear Programming courses for students of the Mathematics Education Study Program. The method used is development research which consists of Preliminary Analysis, Product Prototype, and Assessment. The research subjects were 30 students in the 7th semester of mathematics education and had attended online Linear Programming lectures in the previous semester. Data were collected by conducting written tests, questionnaires, and interviews and analyzed quantitatively descriptively. The results of the written test analysis showed that the students' ability to solve linear programming problems was low. Based on interviews, it is also known that students are not enough just to learn through modules and virtual meetings. Students tend to need learning videos/records to repeat explanations when studying the material independently. Therefore, there is a great need for learning videos that can optimize online learning of Linear Programming courses.